Find the smallest k for which the following statement is always true for n ≥ 1 :
F n ≡ 0 ( m o d 1 0 ) ⟺ F n + k ≡ 0 ( m o d 1 0 )
Where F 1 = 1 , F 2 = 1 and F n = F n − 1 + F n − 2
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
If we write down the first few terms we see that:
And at this point the series repeats, therefore the pattern will continue, and since 15 is the also the first positive n for which F n ≡ 0 , then the answer is 1 5 .
For hypothesis we have F n ≡ 0 ( m o d 1 0 ) . Let's see how it works for next terms.
F n + 1 = F n + F n − 1 ≡ F n − 1 ( m o d 1 0 )
F n + 2 = F n + 1 + F n ≡ F n − 1 ( m o d 1 0 )
F n + 3 = F n + 2 + F n + 1 ≡ 2 F n − 1 ( m o d 1 0 )
It seems that F n + k ≡ F k ⋅ F n − 1 ( m o d 1 0 ) ... Let's prove it by strong induction on k .
Base case: we have just calculated F n and F n + 1 ; thesis holds for both of them.
Induction step:
F n + k + 1 = F n + k + F n + k − 1 for definition
≡ F k ⋅ F n − 1 + F k − 1 ⋅ F n − 1 for inductive hypothesis
= ( F k + F k − 1 ) ⋅ F n − 1
= F k + 1 ⋅ F n − 1 for definition.
Therefore F n + k ≡ F k ⋅ F n − 1 ( m o d 1 0 ) for strong induction on k .
In general it's NOT true that a b ≡ 0 ( m o d m ) ⇒ a ≡ 0 ( m o d m ) ∨ b ≡ 0 ( m o d m ) . But, since the problem's thesis must holds for all n satisfying F n ≡ 0 ( m o d 1 0 ) , it has to be F k ≡ 0 ( m o d 1 0 ) in order to have F n + k ≡ 0 ( m o d 1 0 ) .
With simple calculations we find out that m i n { k ∈ N : F k ≡ 0 ( m o d 1 0 ) } = 1 5 .
By writing this sequence down modulo 10 we can see that we start with 1, 1 and eventually get to 1, 1 again. This means it cycles (only two previous numbers influence the next number). We can also see that between every pair of neighbouring 0s there are 14 numbers therefore the answer.
Problem Loading...
Note Loading...
Set Loading...
Suppose F n ≡ 0 and F n + 1 ≡ x , and x coprime to 10, then we get the following terms by calculating (mod 10):
So we observe that the first term after F n that is 0 (mod 10) is F n + 1 5 . Since 7 x is also coprime to 1 0 , we could repeat the same the argument by induction, so that 0 occurs exactly every 15th term. The initial condition is F 0 = 0 and F 1 = 1 , so right from the start this pattern emerges, so that 1 0 ∣ F n ⇔ 1 5 ∣ n , from which it follows that k=15.